2007
DOI: 10.1183/09031936.00146906
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial density in the vastus lateralis muscle of patients with COPD

Abstract: Skeletal muscle dysfunction is a well-recognised hallmark of chronic obstructive pulmonary disease (COPD) leading to exercise intolerance. The vastus lateralis of COPD patients is characterised by reduced mitochondrial enzyme activity; however, this is not the case in the tibialis anterior. It is, however, unclear whether the compromised oxidative capacity in the vastus is due to reduced mitochondrial volume density. Muscle biopsies were obtained from the vastus lateralis of six COPD patients and four healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 31 publications
10
105
2
2
Order By: Relevance
“…In electron microscopic examination of lung tissues, we demonstrated that mitochondria in bronchial epithelial cells tended to be fragmented in COPD but not in smokers without COPD, suggesting the fission process dominancy of mitochondrial dynamics in COPD pathogenesis. These results are in accordance with previous reports demonstrating that mitochondria in skeletal muscles from COPD patients tended to be smaller in size accompanied by increased ROS production (16,37,39).…”
Section: Discussionsupporting
confidence: 83%
“…In electron microscopic examination of lung tissues, we demonstrated that mitochondria in bronchial epithelial cells tended to be fragmented in COPD but not in smokers without COPD, suggesting the fission process dominancy of mitochondrial dynamics in COPD pathogenesis. These results are in accordance with previous reports demonstrating that mitochondria in skeletal muscles from COPD patients tended to be smaller in size accompanied by increased ROS production (16,37,39).…”
Section: Discussionsupporting
confidence: 83%
“…Mechanical unloading due to physical inactivity contributes to peripheral muscle abnormalities and dysfunction. Muscle weakness in COPD has been reported primarily in thigh musculature (quadriceps, in both men and women [41]), and more recently documented in the ankle dorsiflexors and plantarflexors [42,43]. Taken together, these abnormalities indicate an overall decline in both the contractile and oxidative capacity of lower limbs muscles in patients with COPD [11].…”
Section: Source Of Gait Abnormalities In Copdmentioning
confidence: 80%
“…In the context of earlier 31 P-MRS measurements of CK reaction kinetics in human calf muscle (7) and estimates of mitochondrial spacing in mammalian myocytes (17,42,44), knowledge about D PCr provides important insights into the role that PCr diffusion could play in energy transfer via the putative PCr shuttle mechanism in human muscle.…”
mentioning
confidence: 99%